Multimedia-based Apsimas Learning Media on the Meaning of the Pancasila Precepts in the Community Environment to Improve Students’ Learning Outcomes - Sari, Nur Eka; Witanto, Yuli (Universitas Pendidikan Ganesha, 2024)
The limitations of learning media used during learning take place cause students to be discouraged when learning. In learning, obviously, understudies need learning media to assist them with understanding the material sustainable so the advancement of learning media like learning media